Hydrogen storage studies of mesoporous and titanium based materials - Sheppard, Drew A (Curtin University, 2008)
Concerns over green house gas emissions and their climate change effects have lead to a concerted effort into environmental friendly technologies. One such emphasis has been on the implementation of the hydrogen economy. There are four major impediments to the implementation of a hydrogen economy: hydrogen production, distribution, storage and conversion. This thesis is focused on exploring the hydrogen storage problem. Hydrogen can be stored by a wide range of methods. One of these methods involves using a secondary material that stores hydrogen by either physisorbing hydrogen onto its surfaces or by reacting with it to form a new compound. Of the wide variety of materials that can interact with hydrogen, three different materials were chosen; (1) nano-structured materials of high surface area; mesoporous silica (MCM-41) and titanate nanotubes, and (2) hydrides of Ti-Mg-Ni alloys. Results of the hydrogen on mesoporous silica (MCM-41) showed 1 wt.% H[subscript]2 to a maximum of 2 wt.% H[subscript]2 for 500 to 1060 m2/g surface area, respectively, at 77 K. Doping these samples with Al or Zn did not make an appreciable difference but rather they reduced the surface area available for hydrogen adsorption. Adorption of hydrogen at room temperature was neglifible (0.1 wt.% up to an equilibrium pressure of 5 MPa). Sodium titanate nanotubes showed hydrogen adsorption that increased with increasing hydrogen pressure at 77 K. Hydrogen adsorption reached 0.4 wt.% at an hydrogen equilibrium pressure of 2.6 MPa. Exchange of sodium ions in the titanate nanotubes with Zn and Li did not have an impact on hydrogen adsorption.However, partial substitution of Na ions for H ions resulted in an increase in hydrogen adsorption from 0.4 wt.% to 0.8 wt.% while decreasing the pressure required for maximum hydrogen uptake from 2.6 MPa to 0.5 MPa at 77 K. Desorption from this sample also showed strong hysteresis indicating hydrogen adsorption into the interlayer spacing of the nanotube wall. Hydrogen adsorption at room temperature was negligible for all samples being below 0.1 wt.%, up to a hydrogen equilibrium pressure of 5 MPa. Ti-Mg-Ni alloys are interest as 11 wt.% hydrogen has been reported in the literature; specifically for Ti53Mg47Ni20. Samples with various stoichiometries of Ti, Mg and Ni were produced via balling and their hydrogen sorption properties examined. Measured hydrogen absorption ranged from 2.5 wt.% to 5.0 wt.%. Measurements were hindered by the high temperature (723 K) used during the activation process. The high temperature ensured decomposition of titanium hydride but resulted in the vaporisation and deposition of magnesium on the sample cell filter. This had the duel effect of reducing the total hydrogen absorption and to sporadically block the sample cell filter. However, in those cases where the hydrogen flow was not impeded, absorption kinetics were measured to be extremely rapid. For example, greater than 95 % of the total hydrogen uptake of 3.7 wt.% for the sample ball-milled in the molar ratio of 65:133:20 (Ti:Mg:Ni) occurred within 60 seconds at room temperature.However, the low equilibrium pressure meant a negligible amount of hydrogen could be desorbed at this temperature. X-ray diffraction revealed that after hydriding, the samples comprised varius mixtures of MgH[subscript]2, TiH[subscript]2 and hydrides of the intermetallic compounds Mg[subscript]2Ni and Ti[subscript]2Ni. The amount of each of these hydride phases changed according the intial starting stoichiometries of each sample.